Perempuan Pekerja Migran Non-Reguler: Konflik Hukum Dalam Pengaturan Perdagangan Orang Dan Penyelundupan Orang - Eddyono, Sriwiyanti (UI Scholars Hub, 2021)
This paper analyzes the extent to which Indonesian law regulates the position and protection of irregular women migrant workers and the implication of the arrangement of law for irregular women migrant workers who experience human trafficking and people smuggling. This paper follows up on field findings on human trafficking in the Kalimantan border which was carried out in 2018-2019. This paper finds that there are complications in the regulation on laws and regulations, related to the regulation of Irregular Migrant Workers. Even though the law which is based on international conventions explicitly regulates Non-Regular Migrant Workers (Migrant Workers Convention 1990) and acknowledges the existence and problems of Women Non-Regular Workers (CEDAW), other laws ignore the regulation of trafficking in persons but as problematic migrant workers/PMI.